Lymphocytes as a Biomarker of Frailty Syndrome: A Scoping Review - Navarro-Martínez, Rut (Diseases, 2021)
Frailty is a geriatric syndrome characterized by a decrease in physiological reserve and reduced resistance to stress, as a result of an accumulation of multiple deficits in physiological systems. Frailty increases the vulnerability to adverse events and is associated with the aging process. Several studies show an association between frailty syndrome and altered blood lymphocyte levels, which is therefore potentially useful for monitoring interventions to improve or delay frailty. The main objective of this review is to provide an analysis of the current evidence related to changes in lymphocyte counts and their associations with frailty syndrome. To that end, the literature published in this field until March 2021 was in several databases: PubMed, SCOPUS, and Cochrane. Eighteen studies analyzed the association between lymphocyte counts, lymphocyte subtypes, and frailty syndrome. Eighteen studies were analyzed, and most of them reported associations. Interestingly, the association between frailty syndrome and lower lymphocytes counts appears in different clinical conditions. Further studies are needed to determine the sensitivity of lymphocyte counts and lymphocyte subtypes in the diagnosis and monitoring of frailty syndrome, and for this measure to be used as a biomarker of frailty status.